Pendidikan Kewirausahaan dan Literasi Digital Sebagai Katalis Pengembangan UMKM di Kalangan Mahasiswa - Awaliah Arisyah; Marisa Anggraini; Yulia Novita (CV Muara Edukasi, 2025)
Entrepreneurship education and digital literacy are increasingly recognized as important foundations for the development of student-led micro, small, and medium enterprises (MSMEs), especially in today’s digital-driven economy. This study explores how these two elements work together to strengthen students’ entrepreneurial abilities and support the growth of digitally oriented MSMEs. Using a mixed-method approach, data were obtained from 250 students through structured surveys and complemented by in-depth interviews with 12 key informants, including lecturers, MSME assistants, and active student entrepreneurs. The findings reveal that entrepreneurship education enhances students’ managerial readiness, strengthens their entrepreneurial mindset, and encourages business initiation. Meanwhile, digital literacy contributes to improved mastery of digital marketing, online transaction operations, and the use of data in decision-making. When combined, both variables show a mutually reinforcing influence on the performance of student MSMEs. This research emphasizes the importance of integrating entrepreneurial learning with practical digital skills to build sustainable and innovative student businesses. Several recommendations are proposed, including strengthening curricular content, providing hands-on digital training, and enhancing institutional support for student business incubation programs